Electronic government and the information systems perspective : 6th International Conference, EGOVIS 2017, Lyon, France, August 28-31, 2017, Proceedings /: 6th International Conference, EGOVIS 2017, Lyon, France, August 28-31, 2017, Proceedings. ([2017]) - Unknown
No abstract available